Dreams & goals - Phoenix Films (St. Louis : Phoenix Films [production company] ; Kuala Lumpur : Visual Resources [distributor], 1989)
Clearly defined, written goals are the tools which make purposes achievable. The reasons some people never reach their goals is that they don't think about them. They fail by default
Presenter: Carole Harder
Keywords: Goal (Philosophy).; Dreams